Sustainable Accounting indicators that related with create value for the firm - عبد الله سلمان حسين; وادي سكنة سوادي (Journal of Economics and Administrative Sciences, 2018)
The business environment is witnessing great and rapid developments due to the economic and technological development that has caused damage to human beings, which requires the need to reduce this damage and work to protect the environment and participate in supporting the social aspects. This requires economic resources to be realized by the economic units. Economic development in preserving the environment that has caused damage and supporting the social aspects that preserve human rights, enhance their position and satisfy their needs in society. Global professional organizations, the United Nations and stakeholder representatives have been issuing the Global Reporting Initiative (GRI) to find guidelines for the preparation of sustainability reports according to SASB standards, which instructs economic units to issue sustainability reports so that they can make comparisons with similar units and disclose related matters The relative importance and reporting on the essential aspects of their environmental, social and economic contributions that help them to gain the support of society, and this helps them to continue their work and achieve their goals, thus achieving their values ​​for them and the society and all the owners of the Saliha. The publication of sustainability reports as well as the annual financial report provides sufficient information on all aspects of the economic unit of the stakeholders so that they can know their future vision and direction and current and future strategies. Therefore, they can make good decisions that lead to the expansion of economic units activities that benefit the economic development and society, This leads to the economic growth and social well-being of society as a whole. As demonstrated by sustainability reports prepared by the Economic Units of 2015.